Occupational Health and Safety Practices in Small and Medium-Sized Enterprises in The Construction Sector and A New Model Proposal - Fatih ALTUNTAS; Redvan Ghasemlounıa (Journal of Innovative Science and Engineering)
The aim of the study is to create a model that examines the average occupational safety performance level by considering both occupational health and safety performance in the workplace and occupational health and safety management system performance to improve the level of occupational health and safety in small and medium-sized construction companies. For this purpose, 34 small and medium-sized construction companies located in various cities in the Marmara Region constitute the sample group of the study. The data obtained from the sample group were analyzed using factor analysis and descriptive analysis in the SPSS program and the fuzzy logic method in the MATLAB program. With the fuzzy logic approach, two input variables and one output variable were created and defined with five parameters each. Subsequently, with 25 rules created using the fuzzy approach, the calculated average safety index was obtained at 5.69. It is observed that 18 construction companies, constituting 52.8% of the examined 34 small and medium-sized construction companies, have low safety performance, while 16 construction companies, constituting 47.2%, exhibit high performance